Online food delivery services using online food delivery application: generation Y’s attitude. - Joehan Joehari William; Mohamad Isa Abd Jalil; Geoffrey Harvey Tanakinjal; Low, Irene Jia Wen (Penerbit UMS, 2024)
This study aims to address the gap in prior research by examining the factors influencing generation Y’s attitude toward online food delivery services and purchase intention using online food delivery applications in Malaysia. Data were collected through an online survey where Google form is created and distributed through social media platforms such as WhatsApp, Facebook, and Instagram. The target respondents are generation Y consumers residing in Malaysia. A total of 200 questionnaires have been collected. Statistical Product and Service Solutions (SPSS) version 27 was applied to analyse the information from 200 qualified questionnaires. The result indicates four variables: effort expectancy, time-saving orientation, and social influence that positively impact generation Y’s attitude toward online food delivery services. Generation Y’s attitude towards online food delivery services has a positive impact on generation Y’s purchase intention using online food delivery applications. However, the performance expectancy, price-saving orientation, and information quality does not positively impact generation Y’s attitude towards online food delivery services. Age does not moderate the relationship between generation Y’s attitudes toward online food delivery services and generation Y’s purchase intentions using online food delivery applications in Malaysia. This research contributed additional information to prior studies in a similar area, of which only a handful are addressed from the Malaysian context. This study is also beneficial for future researchers, marketers, and businesses involved in food industry segments.